Market Assessment of Pear Varieties in Serbia Using Fuzzy CRADIS and CRITIC Methods - Puška, Adis; Nedeljković, Miroslav; Prodanović, Radivoj; Vladisavljević, Radovan; Suzić, Radmila (Agriculture (Basel), 2022)
The research deals with the market assessment of pear varieties in Serbia. Market assessment represents the willingness of customers to consume a certain fruit or a certain variety. This research applies a market assessment of pear varieties based on expert decision making. Together with the experts, the criteria and varieties of pears used in the research are determined. Ten criteria and six varieties of pears that are mostly grown in Serbia are used. Experts evaluated pear varieties based on linguistic values according to selected criteria. Based on these values, and using fuzzy logic, the weights of the criteria are first determined using the fuzzy CRITIC method (criteria importance through intercriteria correlation), and pear varieties are ranked using the fuzzy CRADIS method (compromise ranking of alternatives from distance to ideal solution). The obtained results show that the highest rated varieties are Konferans and Viljamovka, while the lowest rated variety is Šampionka. Sensitivity analysis confirms these results. The obtained results will help cultivators and fruit vendors to choose those varieties that will achieve the best market results. This study is conducted to provide guidelines for the use of fuzzy methods in marketing assessment in fruit growing.